Human Resource Costs and Corporate Financial Performance of Listed Deposit Money Banks in Nigeria - Korolo, Akuboere Salome; Korolo, Emmanuel Omolaye (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study investigates the relationship between human resource costs and the corporate financial performance of listed deposit money banks in Nigeria. The specific objectives of the study were to determine whether the director’s remuneration cost, salary & wage cost, and pension and gratuity cost have any effect on the earnings per share of listed deposit money banks in Nigeria. An ex-post facto research design was adopted, and the study used secondary data from the annual reports and statements of account of selected banks listed on the Nigerian Exchange Group for the period 2018–2022. Judgmental sampling techniques were employed to investigate the relationship existing between the variables. The study showed that director's remuneration cost has no significant positive effect on earnings per share of listed deposit money banks in Nigeria, salaries and wages cost have a significant negative effect on earnings per share of listed deposit money banks in Nigeria, and pension and gratuity cost have no significant effect on earnings per share of listed deposit money banks in Nigeria. Generally, this study concludes that there is no significant positive relationship between human resource costs and the corporate financial performance of listed deposit money banks in Nigeria. The study therefore recommends that management should not recruit more staff and should consider retaining only efficient staff. This implies that deposit money banks should downsize their staff and focus on training and re-training the most efficient members of staff.